AI-Driven Crop Monitoring and Yield Prediction: A Comparative Study of Global and Pakistan-Based Agricultural Applications - Ghulam Farooque (Corresponding author); Muhammad Hamza Subhpoto; Ali Muhammad; Arfa; Ali Raza Nayoon; Muhammad Bilal; Iqra Nayoon; Maria (Zealous & Energetic Scholarly Texts, 2026)
The integration of artificial intelligence (AI) into agricultural systems has produced a transformational shift in the precision and scalability of crop monitoring and yield estimation. This study presents a comprehensive comparative analysis of AI-driven agricultural technologies, contrasting global industrial-scale deployments with emerging applications contextualized within Pakistan's predominantly smallholder farming landscape. The study synthesizes evidence from peer-reviewed literature, remote sensing studies, and documented field deployments to evaluate the trajectory of methodological progression from conventional statistical approaches through classical machine learning to state-of-the-art deep learning architectures, including convolutional neural networks (CNN), long short-term memory (LSTM) networks, and vision transformers. Global commercial platforms are reviewed with respect to their AI technologies and monitoring capabilities. Pakistan-specific initiatives are catalogued and critically assessed against international benchmarks. Quantitative performance metrics from peer-reviewed studies reveal that advanced deep learning models achieve R² values of 0.87–0.95 in well-instrumented global contexts, whereas Pakistan-based implementations report R² values in the range of 0.74–0.88, reflecting systemic challenges in data availability, ground truth collection, digital infrastructure, and land fragmentation. The discussion identifies barriers to AI adoption in smallholder contexts and proposes a layered framework for capacity-building, data governance, and transfer learning adaptation. This study concludes that bridging the technology gap requires coordinated investment in national agricultural data infrastructure, international model transfer, and context-specific AI tool development targeting Pakistan's agroclimatic and socioeconomic realities.